Surgery versus concurrent chemoradiotherapy for stage III non-small cell lung cancer: a retrospective study with propensity score matching - Takao Shigenobu; Yuri Taniguchi; Takahiro Suzuki; Yuya Tabuchi; Mizuki Sato; Kazumasa Odagiri; Yukiko Nakamura; Tsuneo Shimokawa; Hiroaki Okamoto; Akira Yoshizu (BMC Cancer)
Abstract Background No study has directly compared the outcomes of surgery and concurrent chemoradiotherapy (cCRT) in patients with stage III non-small cell lung cancer (NSCLC) to date. This study aimed to compare the treatment efficacy of complete resection and definitive cCRT. Methods Patients were recruited in this retrospective study from Yokohama Municipal Citizens’ Hospital between January 2013 and December 2022. We analyzed patients with pathological stage III NSCLC who underwent complete surgical resection and those with clinical stage III NSCLC who underwent definitive cCRT. Propensity score matching was performed to balance baseline clinicopathological factors, and the prognoses of patients in each treatment group were examined using Cox proportional hazards regression. Results Of the 923 patients with NSCLC who underwent surgery, 97 with pathologic stage III NSCLC underwent complete resection (surgery group) and 125 with clinical stage III NSCLC underwent cCRT (cCRT group), of whom 54 (43.2%) received consolidation therapy with durvalumab. Overall survival (OS) was significantly higher in the surgery group than in the cCRT group (5-year OS: 60.5% versus 43.0%), hazard ratio [HR] = 0.585, 95% confidence interval [CI]: 0.390–0.877, p = 0.010). However, no significant difference in OS was found between the two groups after propensity score matching (5-year OS: 59.8% versus 48.1%, HR = 0.728, 95% CI: 0.416–1.277, p = 0.268). Conclusions The outcomes of the surgery and cCRT groups did not significantly differ in the treatment of stage III NSCLC. Appropriate evaluation of the treatment required should be reviewed on a case-by-case basis.